Passion and compassion as strategic drivers for sustainable value creation: An ordonomic perspective on social and ecological entrepreneurship - Markus Beckmann; Ingo Pies; Alexandra von Winning (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2012)
Passion – in the sense of fervent commitment to action – and compassion – understood as sensitive openness for social and ecological concerns – are not a sure formula for business success. Whether social or ecological entrepreneurs, who find themselves under pressure from market competition, experience advantages or disadvantages, depends crucially on the level at which passion and compassion are brought into play. Competitive advantages are possible if entrepreneurial innovators engage in rule-finding discourses and in rule-setting processes that aim at setting free a previously neglected potential for value creation. To illustrate, this article makes use of a case study in order to elucidate the ordonomic 4-box-matrix, which is a valuable orientation tool for strategic management. – – Leidenschaftliches Engagement (,,passion“) und Mitgefühl im Sinn einer besonderen Sensibilität für bislang vernachlässigte Anliegen sozialer oder ökologischer Art (,,compassion“) sind keine Garantie dafür, dass Unternehmen im Marktwettbewerb erfolgreich bestehen können. Ob sie sich positiv oder negativ auswirken, hängt davon ab, ob es Unternehmen gelingt, passion und compassion in Regelfindungsdiskursen und Regelsetzungsprozessen zur Geltung zu bringen, die darauf abzielen, bislang unausgeschöpfte Wertschöpfungspotentiale innovativ freizusetzen. Hierfür wird anhand einer konkreten Fallstudie die ordonomische Vier-Felder-Matrix illustriert, die dem strategischen Management eine wichtige Orientierung zu bieten vermag.
urn:nbn:de:gbv:3:2-17712
Keywords: M14; M21; M40; Q56; 330; Social Entrepreneurship; Value Creation; Stakeholders; Social Dilemmas; Sustainability; Strategic Management; Social Entrepreneuship; Wertschöpfung; Stakeholder; Soziale Dilemmata; Nachhaltigkeit; strategisches Management